2022
DOI: 10.1021/acsphotonics.2c01634
|View full text |Cite
|
Sign up to set email alerts
|

Improved Operation Stability of Colloidal Quantum Dots Photodiodes via Suppressing Ion Migration

Abstract: Solution-processed colloidal quantum dots (CQDs) photodiodes are compatible for monolithic integration with silicon-based readout circuit, enabling high-performance and low-cost infrared imaging. However, operation stability of CQDs photodiodes has rarely been explored, which is one of the main obstacles for CQDs imaging commercialization. Here, we reveal that the performance deterioration of the CQDs photodiodes under strong electric field at high temperature is mainly attributed to ion migration in CQDs film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The high surface‐to‐volume ratio of CQDs makes them susceptible to external factors such as ion migration and oxidation. [ 30,31 ] The results of this study underscore the critical role, in device stability, of a unified emphasis on transport layers and the CQD active layer.…”
Section: Discussionmentioning
confidence: 73%
“…The high surface‐to‐volume ratio of CQDs makes them susceptible to external factors such as ion migration and oxidation. [ 30,31 ] The results of this study underscore the critical role, in device stability, of a unified emphasis on transport layers and the CQD active layer.…”
Section: Discussionmentioning
confidence: 73%
“…Nevertheless, occasionally CdSe, 167,168 CdTe, 169 and HgTe 170 CQDs are also employed as an absorbing material for NIR photodetectors. Metal chalcogenide CQD-based photodetectors with exceptionally high operating characteristics can be fabricated via recent developments in CQD synthesis, 170 air stability improvement, 171 new surface treatment concepts, 172 coupling with plasmonic nanostructure 173 and elimination of interface defects between ETL and CQDs. 174 They work well in many kinds of photodetector configurations, including phototransistors, photodiodes, and photoconductors, and they often have extremely high gain and sensitivity or quick photo-response times.…”
Section: Photophysical Properties Of Cqdsmentioning
confidence: 99%
“…The in-synthesis incorporation of halides has been demonstrated to afford enhanced material stability in the same vein. While the stability of CQDs themselves is important, the device architecture is another important parameter for device stability. It has been found that the halide-capped PbS CQD active layer combined with the thiol-capped back layer affords improved device stability in air. , In addition, physical encapsulation, such as the insertion of polyimide and the infusion of amorphous Al 2 O 3 , can improve the stability of CQD materials and devices. , …”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the halide-capped PbS CQD active layer combined with the thiol-capped back layer affords improved device stability in air. 17,18 In addition, physical encapsulation, such as the insertion of polyimide 19 and the infusion of amorphous Al 2 O 3 , can improve the stability of CQD materials and devices. 20,21 However, little attention has been directed toward the contact between the metal electrode (such as Au) and PbS CQD layers.…”
Section: ■ Introductionmentioning
confidence: 99%